CEP70 Protein Interacts with γ-Tubulin to Localize at the Centrosome and Is Critical for Mitotic Spindle Assembly - Shi, Xingjuan (American Society for Biochemistry and Molecular Biology, 2011)
Deregulation of the mitotic spindle has been implicated in genomic instability, an important aspect of tumorigenesis and malignant transformation. To ensure the fidelity of chromosome transmission, the mitotic spindle is assembled by exquisite mechanisms and orchestrated by centrosomes in animal cells. Centrosomal proteins especially are thought to act coordinately to ensure accurate spindle formation, but the molecular details remain to be investigated. In this study, we report the molecular characterization and functional analysis of a novel centrosomal protein, Cep70. Our data show that Cep70 localizes to the centrosome throughout the cell cycle and binds to the key centrosomal component, γ-tubulin, through the peptide fragments that contain the coiled-coil domains. Our data further reveal that the centrosomal localization pattern of Cep70 is dependent on its interaction with γ-tubulin. Strikingly, Cep70 plays a significant role in the organization of both preexisting and nascent microtubules in interphase cells. In addition, Cep70 is necessary for the organization and orientation of the bipolar spindle during mitosis. These results thus report for the first time the identification of Cep70 as an important centrosomal protein that interacts with γ-tubulin and underscore its critical role in the regulation of mitotic spindle assembly.